Breakthrough SARS-CoV-2 Omicron Variant in Individuals Primed with Heterologous Vaccines Enhances Inhibition Performance of Neutralizing Antibody to BA.2 Parental Lineage - Jidapa Szekely; Piyawut Swangphon; Natthaphon Nanakorn; Panuttha Chaimuti; Teerapat Nualnoi; Paweena Wongwitwichot; Namchoke Somapa; Denpong Somapa; Theerakamol Pengsakul (Vaccines, 2023)
This study aims to analyze the neutralization ability against Omicron parental variants in five clusters of individuals with different Coronavirus disease (COVID-19) immunity backgrounds, including individuals receiving a homologous or heterologous vaccine without prior infection, recovered patients with homologous or heterologous vaccination, and recovery patients without vaccination. Severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) surrogate virus neutralization assay was performed on serum samples. Spearman correlation analysis showed that the percent inhibition against Omicron B.1.1.529 and BA.2 was significantly related to the period of serum collection (r = 0.730 and 0.787, p < 0.001, respectively). Very strong correlation between percent inhibition of neutralizing antibody against Omicron B.1.1.529 and BA.2 variants (rs = 0.973, p < 0.001) was also observed. The neutralizing activity of the sera from recovery patients receiving homologous and heterologous vaccine against the wild-type, B.1.1.529, and BA.2 Omicron variants was significantly higher (p < 0.001) than that of recovery patients without vaccination. This study robustly showed that the breakthrough SARS-CoV-2 Omicron variant in individuals who received homologous and heterologous vaccines had a high level of neutralizing activity against B.1.1.529 and BA.2 parental lineage of XBB subvariants. Therefore, the next-generation COVID-19 vaccine against emerging variants is needed to improve resilience against ongoing variants, particularly for persons who have never been infected.